Al-doped ZnO/Ag/Al-doped ZnO multilayer films with a high figure of merit. Issue 10 (December 2015) - Ho Kim, Jun; Moon, Yoon-Jong; Kim, Sun-Kyung; Yoo, Young-Zo; Seong, Tae-Yeon
Abstract: In this study, we investigated the effects of the Al-doped ZnO (AZO)-layer thickness on the optical and electrical properties of AZO/Ag/AZO multilayer films deposited on glass substrates at room temperature. The optimal AZO/Ag/AZO (36 nm/19 nm/36 nm) multilayer sample exhibited a transmittance of approximately 93% at 550 nm. As the AZO-layer thickness increased from 9 to 45 nm, the carrier concentration gradually decreased from 1.87×10 22 to 6.36×10 21 cm −3, while the sheet resistance slightly increased from 3.86 to 4.47 Ω sq −1 and the charge mobility increased from 24.15 to 25.42 cm 2 V −1 s −1 . The samples had smooth surfaces with a root mean square (RMS) roughness ranging from 0.40 to 1.23 nm. The Haacke figure of merit (FOM) was calculated for the samples as a function of the AZO-layer thickness. The optimal AZO/Ag/AZO multilayer film had the highest FOM of 99.9×10 −3 Ω −1 .